In vivo guiding nitrogen-doped carbon nanozyme for tumor catalytic therapy - Kelong Fan (Nature Portfolio, 2018)
If decorated with the right surface modifications, nanoparticles can function as Trojan horses, transporting cell death-facilitating compounds to tumor cells. Here, the authors prepare a particle with four enzyme-like activities and show that ferritin can direct nanoparticles to tumor cells.